Pyogenic hepatic abscesses secondary to choledocholithiasis eight years post-cholecystectomy: A case report - Umaseh Sivanesan; Vishal Varma; Stefanie Y. Lee (European Journal of Radiology Open, 2020)
Cholecystectomy is the gold standard surgical treatment for acute calculous cholecystitis. Only approximately 0.4 % of these patients subsequently develop choledocholithiasis. The incidence of hepatic abscesses in these patients is unknown, but is likely low, considering there are approximately 2–15 cases of hepatic abscesses per 100,000 people in the US. The authors report the case of a 62-year-old man whose CT scan revealed hepatic abscesses secondary to choledocholithiasis, eight years after a cholecystectomy.